Characterisation of Particulate Matter Emitted from Cofiring of Lignite and Agricultural Residues in a Fixed-Bed Combustor - Nattasut Mantananont; Savitri Garivait; Suthum Patumsawad (The Scientific World Journal)
This study is focused on the emission of fixed bed combustor batch operated. Real-time analyser ELPI (electrical low-pressure impactor) system was used to size-segregated particulate matter emission ranging from 40 nm to 10 μm. The results show that total number concentration were 3.4×103, 1.6×104, and 1.5×105 particles/cm3⋅kgfuel, while total mass of particles were 12.2, 8.0, and 6.5 mg/Nm3⋅kgfuel for combustion of lignite, rice husk and bagasse, respectively. But it can be noticed that cofiring released more particulate matter. Meanwhile it was found that the effect of ratio of over-fired air to total air supply is more pronounced, since decrease in this ratio, the amount of particles are decreased significantly. For particle size distribution, it can be observed that submicron-sized particles dominate and the most prevailing size is in the range: 50 nm <Dp<100 nm, for lignite and agricultural residues. However, during cofiring of fuel mixture at 70% rice husk mass concentration, it is found that there are two major fractions of particle size; 40 nm <Dp<70 nm and 0.2 μm <Dp<0.5 μm. The analysis of particle morphology showed that the isolate shape of submicron particle produced during lignite combustion is characterised by different geometries such as round, capsule, rod, flake-like, whereas the spherical shape is obtained with combustion of rice husk.